Serological and Molecular Evidence of Patients Infected with Anaplasma phagocytophilum in Mexico - Sosa-Gutierrez, Carolina Guadalupe; Cervantes-Castillo, Maria Almudena; Laguna-Gonzalez, Ramon; Lopez-Echeverria, Laura Yareli; Ojeda-Ramírez, Deyanira; Oyervides, Mayra (Diseases, 2021)
Human granulocytic Anaplasmosis (HGA), is a tick-borne infectious disease transmitted by ticks, resulting in acute feverish episodes. The etiological agent is the bacteria Anaplasma phagocytophilum; which is spread by ticks of the genus Ixodes spp. to complete its life cycle. In Mexico, there is only one case report. The primary challenge is understanding how other bacteria affect or overlap with the clinical manifestation of the disease. Sample collection occurred over the period September 2017 through October 2019. Blood samples from human subjects were obtained immediately after they signed consent forms. We analyzed for the presence for A. phagocytophilum by serological (IFA IgG two times) and PCR targeting 16SrRNA and groEL genes, followed by DNA sequencing. All patients with a history of travel abroad were dismissed for this project. In total, 1924 patients participated and of these, 1014 samples across the country were analyzed. Of these, 85 (8.38%) had IFA results that ranged from 1:384 to 1:896. Of the positive samples, 7.10% were used for PCR. Significant clinical manifestations included: dizziness, nausea, petechial, epistaxis, enlarged liver and/or spleen and thrombocytopenia. Hospitalization of at least 1.5 days was necessary for 3.2% of patients. None of the cases analyzed were lethal. This is the first clinical manifestations along with serological test results and molecular analysis confirmed the presence of A. phagocytophilum resulting in HGA in patients from Mexico. Health institutions and medical practitioners in general should include diagnostic testing for HGA among high risk populations and should recognize it as a vector-borne emerging infectious disease in Mexico.